Method for predicting the maximum reliable angle to use in themonostatic-to-bistatic equivalence theorem. - Wilson, Kelce S. (IEEE Antennas & propagation magazine.)
A metric is proposed that allows reliable prediction of the maximum bistatic angle for which the monostatic-to-bistatic equivalence theorem (MBET) can be used. Currently, the theorem leaves the term ?sufficiently smooth? undefined, making selection of the maximum angle somewhat subjective. The proposed metric provides a quantitative evaluation of complexity/smoothness, and relates this to an angle limit based on an empirically derived statistical error profile. That is, the metric allows prediction of the maximum bistatic angle for which the MBET provides less than a 1.5 dB error at a confidence level of 95%. Although the metric is presently only demonstrated for two-dimensional (2D) objects at a single polarization and error value, sufficient experiments following the same process can easily extend the method to three-dimensional objects, arbitrary polarizations, and alternate error tolerances. Such a capability allows for optimization of either monostatic collections used for prediction of bistatic data sets, or bistatic computations interpolated to monostatic results.